Discourse theory and the concept of field: methodological approaches to the analysis of education policies - Kátia Silva Cunha (Red Latinoamericana de Estudios Epistemológicos en Política Educativa, 2016)
This paper weaves a trajectory comprising discourse and the "field‟ category (Bourdieu). We present a few elements of the discourse trajectory, focusing it firstly as a methodological category within the realm of Social Sciences up to its comprehension as a theory, considering the methodological issue that constitutes it. The Discourse Theory sets out to explain how, under which conditions and why the discourse was built, changed or preserved, as well as to show evidence of conflicts, reveal its incompletion, and surface what was split in a determined discursive field, which brings us back to the field category, as a locus of conflict and articulation. In the last section, we present an example of analysis, taking the evaluation policy for Higher Education as the object of study.